The Effect of Implementing the Contextual Teaching Learning (CTL) Approach on the Formation of Students' Physics Behavior - Ilyas, Ilyas; Kaynat, Hina; Salisu, Aminu (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to determine the effect of implementing the Contextual Teaching Learning (CTL) approach on the formation of junior high school students' physics behavior. Methodology: This research is quantitative research with associative causal type. The total research sample was 69 students with a sampling technique using purposive sampling. The instruments used in this research were questionnaires and interviews. The data analysis techniques used in this research are descriptive statistics and inferential statistics. Main Findings: Based on the results of statistical analysis using SPSS 21, it was found that there was an influence of the application of Contextual Teaching (CTL) on the formation of physics behavior in class VIII SMP students with an influence percentage of 42%. With the regression equation Y = 45.508 + 0.363X. This means that if the CTL approach is not used in the physics learning process, the student's physics behavior score will be 45.508. Then, for every 1% increase in the level of the CTL approach, the physics behavior of class VII middle school students will increase by 0.363.l. Novelty/Originality of this study: The findings of this research indicate that this approach in the teaching process is important to use as a means to increase the nuances of learning in the classroom to be more meaningful. The novelty of this research is that it is useful as a means of improving physics teaching and learning strategies in the classroom in order to shape students' positive behavior.